Exploration of the anticandidal mechanism of Cassia spectabilis in debilitating candidiasis - Torey, Angeline; Vijayarathna, Soundararajan; Jothy, Subramanion L.; Gothai, Sivapragasam; Yeng, Chen; Latha, Lachimanan Yoga; Kanwar, Jagat R.; Dharmaraj, Saravanan; Sasidharan, Sreenivasan (Elsevier, 2016)
Candida albicans has become resistant to the commercially available, toxic, and expensive anti-Candida agents that are on the market. These factors force the search for new antifungal agents from natural resources. Cassia spectabilis had been traditionally employed by healers for many generations. The possible mechanisms of the C. spectabilis leaf extract were determined by potassium leakage study and the effect of the extract on the constituents of the cell wall and enzymes as well as the morphological changes on C. albicans cells were studied along with cytotoxicity assays. The cytotoxicity result indicated that the extract is nontoxic as was clearly substantiated by a half maximal inhibitory concentration (IC50) value of 59.10 mg/mL. The treated cells (C. spectabilis extract) demonstrated potassium leakage of 1039 parts per million (ppm) compared to Amphotericin B (AmpB)-treated cells with a released potassium value of 1115 ppm. The effects of the extract on the cell wall proteins illustrated that there were three major types of variations in the expression of treated cell wall proteins: the presence of new proteins, the absence of proteins, and the amount of expressed protein. The activities of two enzymes, a-glucosidase and proteinase, were determined to be significantly high, thereby not fully coinciding with the properties of the antifungal reaction triggered by C. spectabilis. The morphology of C. albicans cells treated with the C. spectabilis extract showed that the cells had abnormalities and were damaged or detached within the microcolonies. Our study verifies C. spectabilis leaf extract as an effective anti-C. albicans agent.